2017
DOI: 10.1073/pnas.1700627114
|View full text |Cite
|
Sign up to set email alerts
|

Host-derived fatty acids activate type VII secretion inStaphylococcus aureus

Abstract: The type VII secretion system (T7SS) of Staphylococcus aureus is a multiprotein complex dedicated to the export of several virulence factors during host infection. This virulence pathway plays a key role in promoting bacterial survival and the long-term persistence of staphylococcal abscess communities. The expression of the T7SS is activated by bacterial interaction with host tissues including blood serum, nasal secretions, and pulmonary surfactant. In this work we identify the major stimulatory factors as ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 41 publications
7
59
1
Order By: Relevance
“…Together with the results obtained using geh and geh lip mutants, this finding implies that an active modification of human LDL-derived fatty acids is required for S. aureus triclosan resistance, reducing the possibility that protection occurs via a nonspecific triclosan-LDL interaction. A recent study using a murine systemic infection model with a fakA mutant found that this mutant is attenuated for colonization of the liver but not the kidneys (73). This finding is intriguing, considering our results demonstrating that FakA is necessary for the ability of S. aureus to utilize LDLs, as the biogenesis of host lipoprotein particles occurs predominantly in the liver.…”
Section: Discussionsupporting
confidence: 44%
“…Together with the results obtained using geh and geh lip mutants, this finding implies that an active modification of human LDL-derived fatty acids is required for S. aureus triclosan resistance, reducing the possibility that protection occurs via a nonspecific triclosan-LDL interaction. A recent study using a murine systemic infection model with a fakA mutant found that this mutant is attenuated for colonization of the liver but not the kidneys (73). This finding is intriguing, considering our results demonstrating that FakA is necessary for the ability of S. aureus to utilize LDLs, as the biogenesis of host lipoprotein particles occurs predominantly in the liver.…”
Section: Discussionsupporting
confidence: 44%
“…Incorporation of SCUFAs into S. aureus membrane has been shown to impact host-pathogen interactions. Lopez et al showed that incorporation of cis SCUFAs from the host into membrane phospholipids activated the type VII secretion system for multiple virulence factors (26). On the other hand, Nguyen et al demonstrated that SCUFAs C16:1, C18:1, and C18:2 were taken up, elongated, and incorporated into membrane phospholipids and the lipid moiety of lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of medium with blood or blood products for antimicrobial susceptibility testing of fastidious pathogens is a common practice (24, 25). The lipid composition of S. aureus has an impact on the interaction of the organism with the host’s defense systems (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…Host-and in vitro-derived exogenous fatty acids were demonstrated to influence bacterial membrane physiology. This resulted in altered phenotypes such as virulence, motility, antimicrobial peptide susceptibility, or biofilm formation [47][48][49][50][51][52]. It was proposed that exogenous polyunsaturated fatty acids were directly incorporated into the bacterial membrane and thus to affect membrane permeability.…”
Section: Discussionmentioning
confidence: 99%